Biography Text E-media for the Tenth-grade High School Students: Prezi Application Development - Ridha Adilla AR; Siti Samhati; Mulyanto Widodo (Online Learning In Educational Research (OLER), 2022)
utilizing Prezi applications on biography text material. The research technique is the research and development approach that employs the DDD-E model (Decide, Design, Develop, and Evaluate). The primary outcome of this research is Indonesian language learning media created with the Prezi application. The quality of Indonesian language learning media utilizing the Prezi application is extremely feasible based on the product development process, which includes product validation by experts (material expert, media expert, and practitioner expert validations). Students from SMAN 5 Bandar Lampung were the research subjects. The researchers also performed a small-scale trial with ten randomly chosen students and a large-scale trial with thirty students. The product feasibility test at SMAN 5 Bandar Lampung yielded a percentage feasibility score of 92.83 (very feasible). The developed media is likely appropriate for use in the learning process. This research, however, was only limited to the development stage. It is envisaged that this media will be tested for effectiveness.